Antibiotic Use and Stewardship in Cystic Fibrosis: A Review for Noncystic Fibrosis Providers. Issue 5 (4th September 2020) - Orsini, Erica; Miranda, Cyndee; Dasenbrook, Elliott
Abstract : Antibiotics form the foundation of comprehensive cystic fibrosis (CF) therapy and are responsible for invaluable gains in life expectancy and quality of life. Although antibiotic stewardship may be perceived to be in conflict with appropriate CF care, there are many potential benefits to antibiotic stewardship in CF. Antimicrobial stewardship teams can provide a collaborative approach to CF care and provide assistance with antibiotic selection, therapeutic drug monitoring, and recommendation of best practices supported by evidenced-based guidelines. The aim of this review is to introduce the rationale for the use of antibiotics in CF care, examine the evidence behind current antibiotic practices, and discuss the potential role of antibiotic stewardship in CF care.